Targeting NAAA counters dopamine neuron loss and symptom progression in mouse models of parkinsonism. (August 2022) - Palese, Francesca; Pontis, Silvia; Realini, Natalia; Torrens, Alexa; Ahmed, Faizy; Assogna, Francesca; Pellicano, Clelia; Bossù, Paola; Spalletta, Gianfranco; Green, Kim; Piomelli, Daniele
Abstract: The lysosomal cysteine hydrolase N -acylethanolamine acid amidase (NAAA) deactivates palmitoylethanolamide (PEA), a lipid-derived PPAR- α agonist that is critically involved in the control of pain and inflammation. In this study, we asked whether NAAA-regulated PEA signaling might contribute to dopamine neuron degeneration and parkinsonism induced by the mitochondrial neurotoxins, 6-hydroxydopamine (6-OHDA) and 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP). In vitro experiments showed that 6-OHDA and MPTP enhanced NAAA expression and lowered PEA content in human SH-SY5Y cells. A similar effect was observed in mouse midbrain dopamine neurons following intra-striatal 6-OHDA injection. Importantly, deletion of the Naaa gene or pharmacological inhibition of NAAA activity substantially attenuated both dopamine neuron death and parkinsonian symptoms in mice treated with 6-OHDA or MPTP. Moreover, NAAA expression was elevated in postmortem brain cortex and premortem blood-derived exosomes from persons with Parkinson's disease compared to age-matched controls. The results identify NAAA-regulated PEA signaling as a molecular control point for dopaminergic neuron survival and a potential target for neuroprotective intervention. Graphical Abstract: ga1